2021
DOI: 10.1101/2021.11.17.465477
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kilohertz Transcranial Magnetic Perturbation (kTMP): A New Non-invasive Method to Modulate Cortical Excitability

Abstract: We report a novel subthreshold non-invasive brain stimulation approach that we refer to as kilohertz transcranial magnetic perturbation, or kTMP. kTMP is a magnetic induction method that delivers kHz-frequency cortical E-fields and, through amplitude modulation of the kHz carrier frequency, may mimic E-fields at physiological frequencies. To evaluate the efficacy of kTMP, we used suprathreshold TMS to elicit motor-evoked potentials (MEP) in a peripheral muscle, comparing the amplitude of the MEPs before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…Recent work has also proposed adapting temporal interference to other modalities, including transcranial magnetic stimulation (TMS) 44,45 . The neurophysiological effects of these methods have not yet been fully characterized, but users will still need to contend with similar issues related to sub-optimal electrode/coil placement and incomplete demodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also proposed adapting temporal interference to other modalities, including transcranial magnetic stimulation (TMS) 44,45 . The neurophysiological effects of these methods have not yet been fully characterized, but users will still need to contend with similar issues related to sub-optimal electrode/coil placement and incomplete demodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also proposed adapting temporal interference to other modalities, especially transcranial magnetic stimulation (TMS) (e.g., Khalifa et al, 2023; Labruna et al, 2023). The neurophysiological effects of these methods have not yet been fully characterized, but users will still need to contend with similar issues related to sub-optimal electrode/coil placement and incomplete demodulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown by Vöröslakos et al [10] in TES, it is very unlikely to achieve focal and deep TMS using two TMS coils. More recently, Labruna et al reported TMS at kilohertz [39]. Nevertheless, the E-field intensity was <10 V/m, making it improbable to elicit a suprathreshold response through temporal summation.…”
Section: Previous Studies Employing High-frequency Pulse Trainsmentioning
confidence: 99%
“…The proposed method requires activating multiple TMS coils at ultra-high frequencies and relatively high intensities, potentially elevating the risk of inducing seizures compared to traditional TMS methods. In the study conducted by Labruna et al, up to 5 kHz pulses were applied, yet these pulses were of notably low intensity (<10 V/m) [39]. A series of studies by Ugawa and colleagues employing the quadri-pulse paradigm offer insights into the safety aspects of ultra-high frequency TMS [41][42][43].…”
Section: Safety Considerationsmentioning
confidence: 99%